Negative Contrast Experience: An Ignatian Appraisal - Mosely, LaReine-Marie ca. 21. Jh. (Horizons, 2014)
In the face of continual and increased human suffering in every corner of the world, good and principled people often do nothing. Edward Schillebeeckx's understanding of negative experiences of contrast begins with outrage at excessive human suffering and is followed by protest and eventual praxis to ameliorate and end the suffering. The author queries whether unconscious bias prevents human beings from seeing this suffering, and suggests that embracing a rigorous Ignatian consciousness examen may correct this impairment.